Transposon display supports transpositional activity of P elements in species of the saltans group of Drosophila - De Setta, Nathalia [UNESP]; Costa, Ana Paula Pimentel; Lopes, Fabrício Ramon [UNESP]; Van Sluys, Marie-Anne; Carareto, Cláudia Márcia Aparecida [UNESP] (Springer Nature, 2007)
Mobilization of two P element subfamilies (canonical and O-type) from Drosophila sturtevanti and D. saltans was evaluated for copy number and transposition activity using the transposon display (TD) technique. Pairwise distances between strains regarding the insertion polymorphism profile were estimated. Amplification of the P element based on copy number estimates was highly variable among the strains (D. sturtevanti, canonical 20.11, O-type 9.00; D. saltans, canonical 16.4, O-type 12.60 insertions, on average). The larger values obtained by TD compared to our previous data by Southern blotting support the higher sensitivity of TD over Southern analysis for estimating transposable element copy numbers. The higher numbers of the canonical P element and the greater divergence in its distribution within the genome of D. sturtevanti (24.8%) compared to the O-type (16.7%), as well as the greater divergence in the distribution of the canonical P element, between the D. sturtevanti (24.8%) and the D. saltans (18.3%) strains, suggest that the canonical element occupies more sites within the D. sturtevanti genome, most probably due to recent transposition activity. These data corroborate the hypothesis that the O-type is the oldest subfamily of P elements in the saltans group and suggest that the canonical P element is or has been transpositionally active until more recently in D. sturtevanti. © Indian Academy of Sciences.
Keywords: Canonical P element; Drosophila saltans; Drosophila sturtevanti; O-type P element; Transposon display; Transposon mobilization; primer DNA; animal; classification; Costa Rica; DNA fingerprinting; Drosophila; genetic polymorphism; genetics; geography; Mexico; polymerase chain reaction; South America; transposon; Animals; DNA Fingerprinting; DNA Primers; DNA Transposable Elements; Geography; Polymerase Chain Reaction; Polymorphism, Genetic; saltans group